Portrait of Student Physical Activity: A Descriptive Study on Indonesia (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
Physical activity is a key component of maintaining adolescent health, yet global monitoring indicates that more than 80% of adolescents fail to meet the World Health Organization (WHO) guideline of engaging in at least 60 minutes of moderate-to-vigorous physical activity each day. This issue is particularly concerning in Southeast Asia, including Indonesia, where only about 20–25% of adolescents achieve the recommended levels, with a declining trend observed in the post-pandemic period. This topic is important to investigate because adolescence is a critical stage for developing long-term healthy lifestyle habits, while physical inactivity increases the risk of obesity, cardiovascular diseases, and reduced physical fitness. This study aims to portray the physical activity patterns of students in Indonesia and contextualize the findings within national and regional frameworks by drawing comparisons with broader conditions in Indonesia. A descriptive qualitative approach with a literature review design was employed, analyzing school documents such as curricula and extracurricular activity programs, alongside national scientific and surveillance literature published between 2015 and 2025. A reflective thematic analysis was used to identify recurring patterns, barriers, and enabling factors. The findings indicate that limited sports facilities, the dominance of academic and religious curricula, and socio-cultural norms serve as major barriers to students’ physical activity. On the other hand, support from physical education teachers, community engagement, and family involvement were identified as key facilitators. The study concludes that innovative school- and community-based strategies are essential to increase student participation in physical activity in schools with limited resources, while providing relevant comparative insights for Indonesia and other countries in Southeast Asia